Governance by algorithms - Francesca Musiani (Internet Policy Review, 2013)
Algorithms are increasingly often cited as one of the fundamental shaping devices of our daily, immersed-in-information existence. Their importance is acknowledged, their performance scrutinised in numerous contexts. Yet, a lot of what constitutes 'algorithms' beyond their broad definition as "encoded procedures for transforming input data into a desired output, based on specified calculations" (Gillespie, 2013) is often taken for granted. This article seeks to contribute to the discussion about 'what algorithms do' and in which ways they are artefacts of governance, providing two examples drawing from the internet and ICT realm: search engine queries and e-commerce websites' recommendations to customers. The question of the relationship between algorithms and rules is likely to occupy an increasingly central role in the study and the practice of internet governance, in terms of both institutions' regulation of algorithms, and algorithms' regulation of our society.
Keywords: 300; Internet governance; Algorithms; Rules; Search engine; Recommendation